COACHING DAN MENTORING BERBASIS KOMUNITAS BELAJAR UNTUK PENGEMBANGAN PROFESIONAL GURU DI SD QURROTA A’YUN PURWAKARTA - Nurul Afifah, Shalha; Nugraha, Mulyawan Safwandy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher professional development is often characterized by short-term training programs that are insufficiently connected to classroom practice. This study aimed to analyze the implementation of coaching and mentoring in teacher professional development at SD Qurrota A’yun Purwakarta, including its implementation process, impacts, and challenges. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews, document analysis, and retrospective observation forms administered via Google Forms involving the principal, vice principal for curriculum, and teachers. Data were analyzed using an interactive process of data reduction, data display, and conclusion drawing. The findings revealed that teacher professional development was implemented through the integration of workshops, In-House Training (IHT), Learning Communities (Kombel), reflective coaching, and peer mentoring. Kombel served as the central mechanism linking formal training with classroom implementation through reflection, collaboration, and instructional planning. The implementation contributed to improved teacher reflectivity, collaboration, and instructional practices, as well as increased student engagement, independence, and responsibility. This study identifies an integrated school-based professional development model that is contextual, collaborative, and sustainable.